Persepsi Pemuda Terhadap Majlis Dzikir Dalam Meminimalisir Kecanduan Game Online Di Dusun Patemon Pamekasan - Fauzi, Nurul; Hotimah, Nur; Sunu, Sunu (STAI Publisistik Thawalib Jakarta, 2022)
The purpose of this study was to determine the youth's perception of Majlis Dhikr in minimizing online Game addiction and to know the role of Majlis Dhikr in minimizing Online Games experienced by the youth of Dusun Patemon Pamekasan. This research uses a qualitative approach with the type of case study. The data sources in this study were community leaders and some residents of Patemon hamlet, West Dempo Village. Data collection procedures used are interviews, observation, and documentation. Data analysis was carried out by data reduction, data presentation, and drawing conclusions. Checking the validity of the data is done through continuous observation, peer checking, and triangulation. The results showed that (1) Youth Perceptions of Majliz Zikir in minimizing addiction to online games greatly appreciated and supported these religious activities so that they could reduce online game addiction (2) The activities of Majlis Zikir in minimizing online game addiction were quite influential, due to the activities The youth's playing time online is reduced in addition to providing insight into the negative impact of online gaming.